The Importance of COVID-19 Testing to Assess Socioeconomic Fatality Drivers and True Case Fatality Rate: Facing the Pandemic or Walking in the Dark? - Ibarra-Armenta, Cristina Isabel; Alarcon-Osuna, Moises Alejandro (Journal of Strategic Innovation and Sustainability, 2021)
Europe and other developed countries have become the center of the pandemic while other developing and less developed regions have a low spread of COVID-19. The case fatality rate (CFR) differs among countries; genetics, health systems, population characteristics, public health, and social measures are believed to be the determinants of such diversity. Through an ordinal probit, cross-section, and panel data models for 71 countries, it is shown that countries with more tests per million inhabitants are also those reporting more cases and deaths, and greater testing helped reduce CFR. However, health infrastructure and population health indicators are not confirmed drives for CFR. Our main finding is that the pandemic concentration in developed nations is highly related to their ability and resources for tracking the pandemic. In conclusion, the true CFR drivers at national levels cannot be estimated without increasing the number of tests per million inhabitants. Also, countries with more testings are identifying the reality of the pandemic while others with fewer testings are still walking in the dark. Lastly, lockdown measures are effective at reducing the mortality rate.